ANXIETY DISORDER IN SOPHIE KINSELLA’S FINDING AUDREY - Wulan, Putri Ambar; Sahri, Zulfan (JOURNAL OF LANGUAGE, 2024)
This study delves into the portrayal of anxiety disorder in Sophie Kinsella’s novel, Finding Audrey. It aims to comprehensively analyze how anxiety disorder is depicted, as well as to explore the underlying causes and resulting effects on the protagonist. Employing psychoanalytic theories pioneered by Sigmund Freud (1964), this research intertwines the realms of psychology and literature to unravel the complexities of the protagonist's condition. Using a descriptive method outlined by Creswell, the study meticulously examines the novel's narrative to extract pertinent data. Through this approach, the research sheds light on various facets of anxiety disorder as portrayed in the novel. Notably, the analysis uncovers instances where the protagonist grapples with manifestations of anxiety, including feelings of threat and fear, as well as corresponding behavioral responses. The findings underscore the multifaceted nature of anxiety disorder, elucidating its nuanced effects on the protagonist's daily life. For instance, the protagonist’s coping mechanism of wearing sunglasses to evade eye contact serves as a tangible representation of her struggle with social interactions. Furthermore, the narrative elucidates how the protagonist’s anxiety manifests in her reluctance to attend school and her pervasive fear of leaving the safety of her home environment. By meticulously examining the interplay between psychological theories and literary representation, this study enriches our understanding of anxiety disorders while illuminating the narrative intricacies of Kinsella’s work.